A hybrid three-dimensionally structured electrode for lithium-ion batteries via 3D printing. (5th April 2017) - Li, Jie; Leu, Ming C.; Panat, Rahul; Park, Jonghyun
Abstract: New hybrid 3D structure electrodes with a high aspect ratio are fabricated through extrusion-based additive manufacturing to achieve high mass loading. This new 3D printed battery exhibits both high areal and specific capacity, thus overcoming the trade-off between the two of the conventional laminated batteries. This excellent battery performance is achieved by introducing a hybrid 3D structure that utilizes the benefits of the existing laminated structure and three-dimensional interdigitated structure. In addition, conventional battery paste components are used optimally to fit the 3D printing process, which eliminates the need for a complicated solvent preparation process required for a typical 3D printing process for battery applications. Using the CR2032 coin cell, the general assembly problem that occurs at the 3D structured electrodes is solved, which means that the proposed hybrid 3D structure can easily be added to the existing lamination structure. This innovative design and fabrication process demonstrates the high areal energy and power density, which is a critical requirement for energy storage systems in transportation and stationary applications. Graphical abstract: Highlights: The new 3D battery has high areal/specific capacity, which overcomes the trade-off between the two in conventional batteries. Superior battery performance is achieved via a new hybrid structure that has advantages of the conventional and 3D structure. Conventional li-ion battery paste is optimized for extrusion-based 3D printing without the need of complex solvent processes.